O conceito de formação na BNCC: uma análise semântica - Ramos, Gabriel Nunes (Universidade do Vale do Rio dos Sinos, 2020)
From the political and social constitution, through the conceptualization of crisis, Modernity and post-modernity, neoliberalism established itself as a network of intelligibilities that starts to dictate, from a market logic, forms of subjectification. In this sense, it is assumed that some fundamental notions for the Education field have been through resignifications, losing some of their humanistic and critical value. Understanding the concept of formation as one of those notions that are at stake in this neoliberal logic, which materializes through curricular policies in the educational field, the following question is justified: What is the understanding that the Base Nacional Comum Curricular has of reflection, autonomy and purpose in relation to the concept of formation, and what can this evidence? Thus, through a semantic analysis of frames of selected sections of the material, it was possible to identify the evocation of the superframes of LEARNING, PROFESSIONAL QUALIFICATION and LIFE PROJECT from lexical units related to the concept of formation. Through the analysis of the superframes, it was possible to recognize that, on a cognitive level, the notions related to the idea of formation are associated with the needs of the contemporary labor market by establishing a highly individualistic character, in addition to a conceptual emptying of the understanding of human formation.
Keywords: Formação; Políticas curriculares; Análise semântica lexical; BNCC; Formation; Curricular policies; Lexical semantic analysis